Evaluating shading effects on photovoltaic modules: Mathematical modeling with ideal, single, and double diodes - Abouyaakoub, Mohcine; Chahboun, Mbarek; Ali, Ali Ait; Mrabet, Aziz El; Hihi, Hicham; Barakat, Souhail (Institute of Advanced Engineering and Science, 2025)
Among the issues that solar systems face is partial shadowing that can be caused by many factors, such as trees, buildings, or clouds. A shaded module will produce less energy, which reduces the power supplied by a solar system based on PV panels. The purpose of this study is to model and simulate photovoltaic modules based on an ideal single and double diode. After that, we will simulate five configurations formed by nine photovoltaic solar panels: series (S), parallel (P), series-parallel (SP), bridge-link (BL), and total-cross-tied (TCT) under uniform and non-uniform cases (center, diagonal, and frame). These five PV solar configurations are compared in terms of short circuit currents (ISC), open circuit voltages (VOC), peak powers (PMP), the voltage and current values corresponding to maximum power (VMP, IMP), mismatch power loss (MPL), fill factor (FF), efficiency ratio (ER), and overall maximum power (OMP). The six PV configurations are simulated, considering the parameters of the STM6-40/36 PV module.